The Inheritance (Nominated play, excerpt) - Yordanova (Rein), Tania (Sledva : NBU Journal of Humanities and Arts, 2020)
A drama that began in 1990 when Annie was born. Already on the first night after her birth, dreams that took on the images of three men visit her. They predict that she is the one who will reveal the family secrets and their souls will be comforted because the dead are said â€žeither good or nothing but the truthâ€. Time is an ally with the dreams. Events follow, but the time changes the years impartially. Ten years later, Annieâ€™s grandmother and father die in a disaster. She, her mother and her brother also end up in the hospital.